(untitled) (Bioagro, 2023)
Saline soils can limit seedling germination and growth of the crops. This research sought to identify whether the cowpea varieties Pingo-de-ouro and Coruja are tolerant to salinity in terms of germination and biomass partitioning. A completely randomized design in a 2 x 4 factorial arrangement, totaling eight treatments with four replications was used. The treatments consisted of two varieties of cowpea in addition to NaCl salinity with four levels of electric conductivity (0.0, 3.3, 6.6 and 9.9 dS∙m-1). The variables analyzed were percentage of germination (PG), first germination count (FGC), germination speed index (GSI), average germination time (AGT), percentage of seedling (PSB), shoot (PSHB), root (PRB) and cotyledon (PCotB) biomass, PCotB/PSB ratio and salinity tolerance index (STI). The Pingo-de-ouro variety showed tolerance to 3.3 dS∙m-1 displaying an increase in PSB and PSHB, while the Coruja variety tolerated 6.6 dS∙m-1 with a more significant investment in PRB. Both displayed no significant statistical reduction in percentage of G, FGC, GSI, AGT, and STI up to 3.3 dS∙m-1 for the Pingo-de-ouro variety and 6.6 dS∙m-1 for the Coruja one. Thus, those genetic materials can be used to breed tolerant plants. The present research also provides results for further studies at physiological, molecular, and field conditions.